2014
DOI: 10.1016/j.bpj.2014.02.033
|View full text |Cite
|
Sign up to set email alerts
|

Shaped Apertures in Photoresist Films Enhance the Lifetime and Mechanical Stability of Suspended Lipid Bilayers

Abstract: Planar lipid bilayers suspended in apertures provide a controlled environment for ion channel studies. However, short lifetimes and poor mechanical stability of suspended bilayers limit the experimental throughput of bilayer electrophysiology experiments. Although bilayers are more stable in smaller apertures, ion channel incorporation through vesicle fusion with the suspended bilayer becomes increasingly difficult. In an alternative bilayer stabilization approach, we have developed shaped apertures in SU8 pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 62 publications
(110 reference statements)
1
62
0
Order By: Relevance
“…and capacitance were calculated considering that the membrane conductance is negligible compared to the conductance of the bulk solution 24,25 . The background capacitance is measured before the formation of the bilayer membrane, and subtracted from the measured total capacitance obtained from the bilayer membrane 26 .…”
Section: Microfluidic Device Formation Microchannels Are Entirely Mamentioning
confidence: 99%
“…and capacitance were calculated considering that the membrane conductance is negligible compared to the conductance of the bulk solution 24,25 . The background capacitance is measured before the formation of the bilayer membrane, and subtracted from the measured total capacitance obtained from the bilayer membrane 26 .…”
Section: Microfluidic Device Formation Microchannels Are Entirely Mamentioning
confidence: 99%
“…KcsA was expressed, purified, and reconstituted into proteoliposomes as previously described. 15,33 The channel/lipid molar ratio in the proteoliposomes was 1/6000. It is known that the lipid composition modulates KcsA activity, 33 therefore the protein was reconstituted in liposomes and characterized in bilayers of a 1:1 lipid mixture of 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC) and 1-palmitoyl-2-oleoylsn-glycero-3-phospho-(1 0 -rac-glycerol) (POPG).…”
Section: A Device Design and Fabricationmentioning
confidence: 99%
“…The use of a nonvolatile hydrocarbon solvent is a common approach not only to improve BLM stability but also to promote channel integration (7)(8)(9)(10)(11)(12)(13)(14)(18)(19)(20)(21)(22)(24)(25)(26)(27)(28)(29). Several researchers reported that the presence of nonvolatile organic solvent in BLMs appeared to promote channel reconstitution (28,29).…”
Section: Introductionmentioning
confidence: 99%